PENGARUH FAKTOR EKSTERNAL, KEPUTUSAN INTERNAL KEUANGAN, DAN FREE CASH FLOW TERHADAP RETURN SAHAM PERUSAHAAN YANG TERDAFTAR PADA INDEKS KOMPAS 100 DI BURSA EFEK INDONESIA PERIODE TAHUN 2009-2013 - Ria Fransisca Ifa Evendy; Deannes Isynuwardhana (Bina Ekonomi, 2015)
One of the main goals of a company is to increase its value. High company’s value will be followed by high welfare of the stockholders. The goal is not only determined by company’s internal factors but also its external factors. The purpose of this research is to analyze the effect of external factors, internal financing decisions, and FCF on the company’s stock return. The sample of this research is 46 companies chosen from the companies that are listed in the Kompas 100 Index for the period of 2009-2013. Data of this research will be analized using descriptive statistics, the coefficient of determination, and regression, using Eviews software. There are two regression that The result of this study indicates that external factors and FCF has no effect on the Price Earning Ratio (PER), while internal financing decisions has impact on PER. If the companies’ value is represented by Capital gain, the external factors, and internal financing decisions has impact on the Capital Gain. FCF has no effect on the Capital Gain. Keywords: External factors, internal, FCF, return.